Our brother beloved: purpose and community in Paul's letter to Philemon - Young, Stephen E. (Baylor University Press, 2021)
Cover -- Half Title Page, Title Page, Copyright, Dedication -- Contents -- Acknowledgments -- Abbreviations -- Introduction: Paul's Letter to Philemon and Slaveries Past and Present -- 1. The Need for a New Reading of Paul's Letter to Philemon -- 2. Reading in Search of Social Impact: A New Approach to Paul's Letter to Philemon -- 3. Rereading Paul's Letter to Philemon: Positioning Brother Onesimus within the Christian Community -- 4. Welcoming Brother Onesimus: Becoming a Community of Deliverance -- Excursus: Would It Have Been Too Problematic for Philemon to Manumit Onesimus? -- Bibliography -- Index of Authors -- Index of Biblical and Other Ancient Sources.